A solid phase approach to oligomers of carbohydrate amino-acids: Secondary structure in a trimeric furanose carbopeptoid - Long, D; Smith, M; Marquess, D; Claridge, T; Fleet, G (1998)
The synthesis of oligomers of a C-arabinofuranosyl carbohydrate amino acid on a polystyrene support functionalised with a Rink linker is reported. Cleavage from the solid support gives ready access to dimeric and trimeric carbopeptides bearing a C-terminal carboxamide. Investigations into the solution structure of these novel carbopeptoids utilising 1H NMR indicate that they adopt well defined conformations based around a repeating β-turn like structure stabilised by (i, i-2) inter-residue hydrogen bonds.